Religion and the new immigrants : how faith communities form our newest citizens - Foley, Michael W. 1945-; Hoge, Dean R., 1937- (New York : Oxford University Press, 2007)
"The explosive growth of the immigrant population since the 1960s has raised concerns about its impact on public life, but only recently have scholars begun to ask. how religion affects the immigrant experience in our society. In Religion and the New Immigrants, Michael W. Foley and Dean R. Hoge assess the role of local worship communities in promoting civic engagement among recent immigrants to the United States. The product of a three-year study on immigrant worship communities in the Washington, D.C., area, the book explores the diverse ways in which such communities build social capital among their members, provide social services, develop the "civic skills" of members, and shape immigrants' identities."--BOOK JACKET.
1. Becoming American -- 2. Profiles in diversity -- 3. Sources of social capital -- 4. Immigrant worship communities in the public square -- 5. Building civic skills -- 6. Who we are -- 7. Conclusion.
Includes bibliographical references and index.
Keywords: Church work with immigrants -- United States